Interpretation of 3D high resolution seismic data collected over an IOCG deposit in South Australia - Hossain, M.; Urosevic, M.; Kepic, Anton (Australian Society of Exploration Geophysicists, 2015)
A 3D high–resolution seismic dataset was acquired to investigate typically complex IOCG deposits in Hillside, South Australia. Petrophysical data measured from the core samples and the density data supplied by the mining company were utilised during the volumetric interpretation. However, petrophysical data show that the boundaries between gabbro and metasediments may not generate acoustic impedance contrast to be clearly detected by seismic reflection method. The base of the top cover is mappable throughout the cube and the tops of the major formations have agreement with magnetic data. The faults extracted from the seismic volume using ant-tracking attribute have good agreement with the company supplied geological interpretation based on the drilling information.